Radiation Induced Localised Bullous Pemphigoid - Venkatesan S; Thappa D M; Souza M D; Ratnakar C (Wolters Kluwer Medknow Publications, 1998)
A rare case of radiation induced localized bullous pemphigoid is described in a 42 year old woman having left parotid gland carcinoma.